The risk factors of hypertension in children at Private Middle School IT Jannatul Firdaus in coastal area - Irfan Sazali Nasution; Muhamad Habib Nurwahdan; Muhammad Husin Pangaribuan; Afzidan Lufthi Amaryu Marpaung; Iswar Saputra Nasution; Dimas Septiadi (Universitas Muhammadiyah Enrekang, 2025)
prevalence of hypertension in children continues to rise globally, including in coastal areas that face specific challenges in terms of healthcare access, education, and lifestyle. This study aims to identify the factors associated with the risk of hypertension among 7th-grade students at SMP Swasta IT Jannatul Firdaus, Perlis Village. The study used a descriptive qualitative design with a case study approach. Data were collected through in-depth interviews with students, teachers, and the school principal, as well as direct observation in the school environment. The instruments used included interview guidelines and observation notes. Data were analyzed using thematic analysis. The results showed that most students had habits of consuming high-salt foods, skipping breakfast regularly, and engaging in minimal physical activity. The school did not yet have specific health programs for early hypertension detection or nutrition education. Additionally, the low socioeconomic status of families influenced students' food choices and lifestyle. The conclusion of this study is that an unhealthy diet, lack of physical activity, insufficient health education, and poor family socioeconomic conditions are significant factors contributing to the risk of hypertension in children. Collaborative intervention among schools, families, and communities is necessary to create an environment that supports healthy living habits from an early age. Keywords: Childhood hypertension; Risk factors; Lifestyle; Coastal; School.